Использование графической фасилитации как метода повышения эффективности взаимодействия во время обучения будущих менеджеров и психологов - Шаполова, Виктория Валерьевна (Impressum, 2020)
The article discusses the main features of the use of graphic facilitation in the process of training future managers and psychologists. The reasons for the rare use of the method of graphic facilitation in the learning process are identified. A positive effect on the learning process of visualization methods for educational material has been established.
Keywords: графическая фасилитация; процесс обучения будущих менеджеров; интерактивные технологии обучения; методы визуализации; методы визуальной коммуникации